Analisis Sektor Unggulan Dalam Meningkatkan Perekonomian Kabupaten Pacitan Tahun 2011-2015 - SUCIATI, TRIAS DIAN, Ir. Maulidyah Indira Hasmarini M.S (2017)
This research titled " Analysis of the leading sector in improving the economy of Pacitan District Year 2011-2015". The purpose of this research is to analyze the leading sectors and classify the economic growth of Pacitan district of the year 2011-2015. The Data used in this research is a secondary data in the form of PDRB Pacitan district and the Province of East Java on prices constant 2010 2011-2015 period obtained from the Central Statistics Agency (BPS) Pacitan District and East Java Province. Analysis Tool that is used is a Location Quantient (LQ), shit share Esteban Marquillas, and Klassen typology. The results of research using Location Quantient (LQ), indicates that the economy of Pacitan district dominated eight sectors that become base sector, which have substantial value of the highest coefficient is the agricultural sector, forestry and fishing . While using the shift share Esteban Marquillas analysis with data 2011-2015 leading sector Pacitan district is the agricultural sector, forestry, fisheries and because it has the value of Aij and C'ij biggest and positive. Klassen typology analysis shows the economy Pacitan District when compared with East Java Province agricultural sector, forestry, fisheries and is located on the forward sector and growing fast.